2008
DOI: 10.1108/02640470810879527
|View full text |Cite
|
Sign up to set email alerts
|

Preserving digital local news

Abstract: Much local news-important documentation of local history-is being lost. The fact that a lot of news media is now available digitally, presents new opportunities but also new challenges for such preservation. We explore issues and approaches for collection and management of born digital local news.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…2,3 This price can cause battery packs to cost in excess of $10,000 per vehicle and account for 30-50% of total vehicle cost. 4 Decreasing the price of the battery pack will be extremely important in making EVs price competitive in the automobile market.…”
mentioning
confidence: 99%
“…2,3 This price can cause battery packs to cost in excess of $10,000 per vehicle and account for 30-50% of total vehicle cost. 4 Decreasing the price of the battery pack will be extremely important in making EVs price competitive in the automobile market.…”
mentioning
confidence: 99%
“…In addition, the news images do not only provide contextual evidence for the history, they are also a record of the filming industry in a moment of history (p. 22). However, there is no key effort exerted to preserve the news archives, and hence, the "draft of history" is lost (Allen and Johnson, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The lack of resources has been a challenge to the preservation of the news archives. Digitalisation of news media brings new opportunities to preserve the historic resources (Allen and Johnson, 2008), however, the possible solution comes with new challenges, technically and in other social and political aspects of the society. Thus, Alysen's (2001) research of archival television concluded with a reminder: Media scholars have a significant, if generally unacknowledged, interest in the legal standing of broadcast material because, without the legislative protection of compulsory deposit of audiovisual materials, large amounts of broadcast materials will continue to be out of the reach of the research community.…”
Section: Literature Reviewmentioning
confidence: 99%
“…News and media organizations must also develop an achievable plan for systematic curation of archived content. It is a critical component for creating search indexes for content, as well as determining what should be saved and why (Allen & Johnson, 2008).…”
Section: Practical Implicationsmentioning
confidence: 99%